Toxicity of Suaeda maritima (L) against the Scirpophaga incertulas (W) and Xanthomonas oryzae pv. oryzae (Xoo) disease and its non-target effect on earthworm, Eisenia fetida Savigny. (2nd January 2022) - Sivanesh, Haridoss; Shyam Sundar, Narayanan; Senthil-Nathan, Sengottayan; Stanley-Raja, Vethamonickam; Ramasubramanian, Ramakrishnan; Karthi, Sengodan; Chanthini, Kanagaraj Muthu-Pandian; Almoallim, Hesham Saleh M.; Alharbi, Sulaiman Ali
Abstract: In this study, the botanical pesticide Suaeda maritima (L) leaf extract was evaluated against the yellow stem borer (YSB), Scirpophaga incertulas Walker (Lepidoptera: Pyralidae), and bacterial leaf blight disease Xanthomonas oryzae pv. oryzae (Xoo), of rice. S. maritima leaves were powdered and subjected to various organic solvents, like petroleum ether, ethyl acetate, and methanol based on the polarity, in which ethyl acetate extract of S. maritima produced significant mortality rate against the YSB larvae in a dose dependent manner and also affected the development and feeding activity of the larvae. The extracts also displayed an effective disease control against bacterial blight of Xoo. The gas chromatography–mass spectrometry (GC–MS) analysis of the ethyl acetate extract revealed the presence of nine vital compounds. We have observed the extract is safe to non-target organisms, as they did not cause any toxicity to the earthworm Eisenia foetida . Therefore, these findings suggest that S. maritima can be used as effective pest control agent against disease and pest of rice.